2003
DOI: 10.1152/ajpheart.00834.2002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cortisol on norepinephrine-mediated contractions in ovine uterine arteries

Abstract: Cortisol potentiated norepinephrine (NE)-mediated contractions in ovine uterine arteries (UA). We tested the hypothesis that cortisol regulated alpha(1)-adrenoceptor-mediated pharmacomechanical coupling differentially in nonpregnant UA (NUA) and pregnant UA (PUA). Cortisol (10 ng/ml for 24 h) significantly increased contractile coupling efficiency of alpha(1)-adrenoceptors in NUA, but increased alpha(1)-adrenoceptor density in PUA. Cortisol potentiated NE-induced inositol 1,4,5-trisphosphate [Ins(1,4,5)P(3)] s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
20
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 49 publications
8
20
0
Order By: Relevance
“…The finding that neither 5-HT-nor KCl-induced Ca 2ϩ mobilization and contractions were different between nonpregnant and pregnant uterine arteries suggests that the pregnancy-associated change in uterine artery contractility is selective to ␣-adrenergic stimulation. The increased ␣-adrenergic-mediated contractions in the pregnant uterine artery are consistent with our previous results [13,14] and those of others in sheep [16] and rats [17][18][19]. These results suggest that decreased vascular tone in the uterine artery in pregnancy is accompanied by an increase in vasoconstriction reserve and contractile capability to ␣-adrenergic stimulation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The finding that neither 5-HT-nor KCl-induced Ca 2ϩ mobilization and contractions were different between nonpregnant and pregnant uterine arteries suggests that the pregnancy-associated change in uterine artery contractility is selective to ␣-adrenergic stimulation. The increased ␣-adrenergic-mediated contractions in the pregnant uterine artery are consistent with our previous results [13,14] and those of others in sheep [16] and rats [17][18][19]. These results suggest that decreased vascular tone in the uterine artery in pregnancy is accompanied by an increase in vasoconstriction reserve and contractile capability to ␣-adrenergic stimulation.…”
Section: Discussionsupporting
confidence: 92%
“…Simultaneously, measurement of contractile tension and [Ca 2ϩ ] i in the same tissue was conducted as described previously [11,13,14]. Briefly, the arterial rings were attached to an isometric force transducer in a 5-ml tissue bath mounted on an intracellular Ca 2ϩ analyzer (model CAF-110, Jasco, Tokyo, Japan).…”
Section: Simultaneous Measurement Of [Ca 2ϩ ] I and Tensionmentioning
confidence: 99%
“…The finding that for each pressure step uterine arteries during pregnancy developed less tone at given [Ca 2ϩ ] i , compared with those of nonpregnant sheep, indicates that pregnancy attenuates Ca 2ϩ sensitivity of the uterine artery in response to pressure. Similar findings were obtained in previous studies (53,59) of isometric tension of uterine arterial rings loaded with fura-2, in which the ␣ 1 -adrenoceptor-mediated tension/[Ca 2ϩ ] i relationship in uterine arteries during pregnancy was significantly suppressed.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with the present study, previous studies suggested a transition from thinfilament to thick-filament regulatory mechanisms in the uterine artery during pregnancy and that the Ca 2ϩ -dependent thick-filament pathway, i.e., changes in LC 20 phosphorylation, predominated in ␣ 1 -adrenoceptor-mediated contractions in pregnant uterine arteries (Annibale et al, 1989(Annibale et al, , 1990Xiao and Zhang, 2005). This is supported by the findings of increased ␣ 1 -adrenoceptor densities and synthesis of inositol-1,4,5-trisphosphate in pregnant, compared with nonpregnant, uterine arteries (Xiao et al, 2003).…”
Section: Discussionsupporting
confidence: 55%